Nanopyramid-based absorber to boost the efficiency of InGaN solar cells. (15th September 2019) - El Huni, Walid; Karrakchou, Soufiane; Halfaya, Yacine; Arif, Muhammad; Jordan, Matthew B.; Puybaret, Renaud; Ayari, Taha; Ennakrachi, Houda; Bishop, Chris; Gautier, Simon; Ahaitouf, Ali; Voss, Paul L.; et al.
Highlights: InGaN nano-pyramid absorber is shown to release the usual challenging constraint on p-GaN doping. SiO2 mask is shown to help trap light into the nanopyramids leading to a larger efficiency. Nanopyramid-based solar cell lead to an efficiency at least twice that of planar solar cell. Abstract: InGaN nano-structures, grown using nano selective area growth, have been shown to exhibit high crystalline quality, even for high In content InGaN alloy, and reduced polarization charge effect. They are thus very attractive for the realization of high efficiency solar cells. Compared to planar InGaN absorbers, nanopyramid-based absorbers are shown to relax the usual challenging constraint on the doping of the p-GaN layer, which would be needed to overcome the polarization-induced electric field. NP-based solar cells maintain the same performance with ten times lower p-GaN doping. Furthermore, the SiO2 mask used for selective area growth of the nanopyramids is shown to help trap light into the nanopyramids, leading to increased optical absorption and thus efficiency. Last, InGaN nanopyramid absorber-based solar cells can allow for a higher InGaN residual donor concentration than that of the planar InGaN solar cells. Overall, an optimized In0.3 Ga0.7 N nanopyramid-based solar cell can lead to an efficiency twice than that of a planar InGaN-based solar cells with standard p- and n-GaN doping level. As a proof of concept, an In0.09 Ga0.91 N nanopyramid-based solar cell has been fabricated and is shown to have larger short circuit photocurrent and open circuit voltage than a state of the art In0.08 Ga0.92 N-based planar solar cell.